Influence of Seawater and Discard Brine on the Dissolution of Copper Ore and Copper Concentrate - Velasquez-Yevenes, L (Elsevier B.V., 2018)
It is well known that the Chilean mining industry is facing a shortage of water resources for the sustainable operation not only of existing plants but also of future projects. In addition, the depletion of oxide ores and those containing secondary sulfide copper will leave chalcopyrite ores as the main source of copper for future plants. To assure a sustainable hydrometallurgy plant, alternative water resources such as seawater and discard brine from desalination plants should be used together with a leaching process that can enhance the dissolution of chalcopyrite. This paper reports a study on the dissolution kinetics of finely ground copper oxide ore, chalcopyrite ore, and chalcopyrite concentrate leached in shake flasks, agitated reactors and columns using seawater and discard brine as the leaching solution. The type of chloride solution did not affect the dissolution of the copper oxide mineral. Regardless of the chloride solution used in the leaching test stirred at room temperature, the chalcopyrite dissolution did not exceed 4%, but increased to 90% when the temperature was increased to 50 °C. Column leaching of chalcopyrite ore with a P80 of 5 mm achieved a maximum dissolution of 43% of copper using discard brine at ambient temperature. The results show that curing time of the packed bed before the commencement of column irrigation and intermittent irrigation during leaching appeared to be important parameters to enhance dissolution of copper. Less irrigation time and more resting time can be beneficial for an industrial-scale heap leach plant. © 2018 Elsevier B.V.